Early Breastfeeding Initiation (EBFI) Knowledge: Concept Paper (International Journal of Scientific Research and Management (IJSRM), 2017)
The Early breastfeeding initiation means practical giving of the breast milk to the baby soon after delivery that is in the first hour. Knowledge is defined as a true and justifiable phenomenon. The goal of the researchers in writing in this paper was to have an in depth description of knowledge regarding early breastfeeding initiation for the purpose of measuring and evaluating performance of nurse midwives performance. Concept analysis model postulated by Walker and Avant was used in helping describing the concept of interest. The researchers conducted literature search in a month’s time using, breastfeeding journals, Journals of Nursing Philosophy Cochrane data base, Pub- med and MEDLINE as search engines. Thirty two studies that were found relevant to the concept of interest were included in the description of EBFI knowledge. Early breastfeeding initiation knowledge was cognitively appraised in almost all studies.